2020
DOI: 10.3390/ijms21145168
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: The Rollercoaster of Fibrin(Ogen), D-Dimer, Von Willebrand Factor, P-Selectin and Their Interactions with Endothelial Cells, Platelets and Erythrocytes

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2), also known as coronavirus disease 2019 (COVID-19)-induced infection, is strongly associated with various coagulopathies that may result in either bleeding and thrombocytopenia or hypercoagulation and thrombosis. Thrombotic and bleeding or thrombotic pathologies are significant accompaniments to acute respiratory syndrome and lung complications in COVID-19. Thrombotic events and bleeding often occur in subjects with weak constitutions, multiple risk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 166 publications
(369 reference statements)
5
154
0
7
Order By: Relevance
“…Figure 6E-H are micrographs to show how, in some instances, the fibrin(ogen) deposits aggregate to erythrocytes. We previously reported that spontaneous clotlets are present in platelet-poor plasma (PPP) of COVID-19 patients and that these clotlets have an amyloid structure, as shown using the fluorescent stain ThT [14]. Here, we show these deposits with SEM micrographs, where we find these amyloid deposits in a WB smear (without the addition of thrombin).…”
Section: Scanning Electron Microscopy Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Figure 6E-H are micrographs to show how, in some instances, the fibrin(ogen) deposits aggregate to erythrocytes. We previously reported that spontaneous clotlets are present in platelet-poor plasma (PPP) of COVID-19 patients and that these clotlets have an amyloid structure, as shown using the fluorescent stain ThT [14]. Here, we show these deposits with SEM micrographs, where we find these amyloid deposits in a WB smear (without the addition of thrombin).…”
Section: Scanning Electron Microscopy Resultssupporting
confidence: 51%
“…Such fusions between membranes can be facilitated by P-selectin when present on the platelet membrane. When on the platelet membrane, P-selectin is known to act as adhesion receptor, where it promotes platelet-platelet, platelet-endothelial cells, or platelet-erythrocyte adhesions [14,39]. Figure 2A,B shows scanning electron micrographs from healthy erythrocytes ( Figure 2A) and platelets ( Figure 2B), while Figure 3A-H show platelets from COVID-19 patients.…”
Section: Scanning Electron Microscopy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, levels of vWF and Factor VIII are directly linked to the severity of thrombosis and the ensuing stroke [ 62 , 63 ]. In addition, these appear to be common in COVID-19 patients, where they contribute to VTE [ 64 , 65 ]. Alarmingly, a young and asymptomatic SARS-CoV-2-infected patient who showed increased FVIII and vWF levels without any sign of hyperinflammatory state or blood coagulation activation suffered a stroke [ 66 ].…”
Section: Hemostatic Modulatory Properties Of Resveratrolmentioning
confidence: 99%
“…Lung biopsy and autopsy findings indicate that COVID-19 is associated with an accumulation of cell-free protein-rich exudate in the alveoli, alveolar wall thickening, and inflammation (accumulation of immune cells) [8][9][10][11][12][13]. COVID-19 patients are also at risk of disseminated intravascular coagulation and deposition of fibrin clots in the lungs [8,9,[12][13][14]. In both animal models and COVID-19 patients, there is a consistent accumulation of macrophages in the lungs, whereas increased numbers of lung neutrophils appear to be associated with comorbidities such as pneumonia [12,15,16].…”
Section: Introductionmentioning
confidence: 99%